Sistem Monitoring pH dan Suhu Pada Fermentasi Kopi Berbasis Internet of Things - Bagus Irfanzah Arda Nugraha; Rudi Susanto; Mira Erlinawati (G-Tech: Jurnal Teknologi Terapan, 2024)
Fermentation in coffee is a stage of coffee processing that affects the formation of coffee taste. At the current case study site, the fermentation results are still inconsistent in each processing due to the lack of monitoring of temperature and pH using measuring instruments. The purpose of this research is to create a real-time Internet of Things (IoT)-based pH and temperature monitoring system for the coffee fermentation process so that fermentation can be carried out optimally. In this study, a prototype method is used in its development. The system uses a microcontroller using a DS18b20 temperature sensor and a pH 4502c sensor and uses a buzzer as an alarm control when fermentation has been completed. Then from the tests carried out on this coffee fermentation monitoring device, it shows that the pH sensor has an error value of 1.36% and an accuracy rate of 98.64%, and the temperature sensor has an error value of 1.32% and an accuracy rate of 98.68%. The test results show that the tool works well.